Copper-catalyzed arylation of alkyl halides with arylaluminum reagents - Shrestha, Bijay; Giri, Ramesh (Beilstein Journal of Organic Chemistry, 2015)
We report a Cu-catalyzed coupling between triarylaluminum reagents and alkyl halides to form arylalkanes. The reaction proceeds in the presence of N,N,N’,N’-tetramethyl-o-phenylenediamine (NN-1) as a ligand in combination with CuI as a catalyst. This catalyst system enables the coupling of primary alkyl iodides and bromides with electron-neutral and electron-rich triarylaluminum reagents and affords the cross-coupled products in good to excellent yields.
Keywords: alkylation; arylalkanes; copper; cross-coupling; organoaluminum